Pendampingan Pembuatan Media Pembelajaran Interaktif Ispring Presenter Berbasis HTML 5 - Nur Indah Rahmawati; Fertilia Ikashaum; Sri Wahyuni; Edo Dwi Cahyo (Edumedia Solution, 2022)
The use of technology-based learning media is a common thing to be developed during the pandemic. This learning media must be able to accommodate the needs of students from the cognitive side and the side of student motivation in learning. The implementation of interesting learning is the key for teachers and students so they don't get bored in the routine of learning from home. Therefore, training on making interactive media for teachers at SD MI Banjarsari Metro Utara is very necessary. This activity uses the ABCD approach. The results of this activity are interactive learning media using ispring presenters that are ready to use and can be accessed from any mobile device using HTLM 5 technology.